The inclusion of disability within efforts to address menstrual health during humanitarian emergencies: A systematized review - Wilbur, Jane; Clemens, Felicity; Sweet, Elisabeth; Banks, Lena Morgon; Morrison, Chloe (Frontiers in Water, 2022)
INTRODUCTION Women and girls with disabilities may be excluded from efforts to achieve menstrual health during emergencies. The review objectives were to 1) identify and map the scope of available evidence on the inclusion of disability in menstrual health during emergencies and 2) understand its focus in comparison to menstrual health for people without disabilities in emergencies. METHODS Eligible papers covered all regions and emergencies. Peer-reviewed papers were identified by conducting searches, in February 2020 and August 2021, across six online databases (PubMed, MEDLINE, EMBASE, Global Health, ReliefWeb, and Cinahal Plus); grey literature was identified through OpenGrey, Grey Literature Report, Google Scholar, and Million Short. Eligible papers included data on menstrual health for women and girls with and without disabilities in emergencies. RESULTS Fifty-one papers were included; most focused on Southern Asia and man-made hazards. Nineteen papers contained primary research, whilst 32 did not. Four of the former were published in peer-reviewed journals; 34 papers were high quality. Only 26 papers mentioned menstrual health and disability in humanitarian settings, but the discussion was fleeting and incredibly light. Social support, behavioural expectations, knowledge, housing, shelter, water and sanitation infrastructure, disposal facilities, menstrual material availability, and affordability were investigated. Women and girls with disabilities rarely participated in menstrual health efforts, experienced reduced social support, and were less able to access water, sanitation and hygiene facilities, including disposal facilities. Cash transfers and hygiene kit distribution points were often inaccessible for people with disabilities; few outreach schemes existed. Hygiene kits provided were not always appropriate for people with disabilities. Caregivers (all genders) require but lack guidance about how to support an individual with disabilities to manage menstruation. CONCLUSIONS Minimal evidence exists on menstrual health and disabilities in emergencies; what does exist rarely directly involves women and girls with disabilities or their caregivers. Deliberate action must be taken to generate data about their menstrual health requirements during humanitarian crises and develop subsequent evidence-based solutions. All efforts must be made in meaningful participation with women and girls with disabilities and their caregivers to ensure interventions are appropriate. Systematic review registration: PROSPERO CRD42021250937.